Dampak Peristiwa Pidato Kemenangan Joe Biden Terhadap Abnormal Return Saham Pada Sub Sektor Logam dan Mineral - Yumna Sekar Utami; Wahyudi Wahyudi (Politeknik Ganesha Medan, 2022)
Abnormal returns can be influenced by political events that occur either in a country or in other countries. The momentum of the presidential election is one of the political events that can trigger investor reactions. One of the political events that is used as the object of this research is the event of Joe Biden's victory speech. This study is a quantitative study conducted to determine whether the events of Joe Biden's victory speech affect abnormal returns. Metals and minerals sub-sector stocks are the objects used in this research. A significance of 5% is used in this study to test the hypothesis with IBM SPSS Statistics 23 software with the different test methods of one sample t-test and paired sample t-test. The results of the study are (1) there are abnormal returns in the period before Joe Biden's victory speech on the 13th day, 11th day, 7th day, and 3rd day with negative abnormal returns, (2) there are abnormal returns. returns in the period after Joe Biden's victory speech on the 1st day, 2nd day, 4th day, 9th day, and 12th day with abnormal returns on the first day are positive. Then, for the 2nd day, the 4th day, the 9th day, and the 12th day there were negative abnormal returns, and (3) there was no difference in abnormal returns before and after Joe Biden's victory speech.